(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The study was conducted to assess the economics of local chicken production in some selected local government areas of Kano State, Nigeria. Multistage sampling procedure was used to collect data from 104 household farmers. Descriptive statistics and gross margin analysis were employed in achieving the objectives of the study. The results of the study revealed that local chicken farmers in the study area had a mean age of 40.4 years. While majority (61.54% and 87.5%) of them were females and married respectively with a mean household size of 7 members. The study further disclosed that 58.7% of the local chicken farmers had form of formal education with an average monthly income of ₦36, 653.3. The results also showed that the average total variable cost was ₦548.33, the average gross income was ₦1200, and the gross margin of ₦651.67 while the return on capital invested was 1.18. Finally, the major constraints associated with local chicken production are instability of market price (89.42%), inadequate capital (82.69%) and inadequate institutional support (60.58%). It is concluded that local chicken production in the study area is profitable. It is recommended that the community based financial outlet should support local chicken producers in providing adequate capital to produce at commercial level; adjust the utilization of inputs in such a way that reduces the cost of production thus, raises profit.